Seasonal comparison of carrion volatiles in decomposition soil using comprehensive two-dimensional gas chromatography – time of flight mass spectrometry. Issue 2 (5th December 2014) - Perrault, Katelynn A.; Rai, Tapan; Stuart, Barbara H.; Forbes, Shari L.
Abstract : This study examines the effects of extrinsic variables (weather, soil characteristics, etc. ) on the variation in volatiles produced during carrion decomposition during Australian summer and winter seasons. Abstract : Increased characterisation of decomposition odour has improved existing knowledge regarding the decomposition volatile organic compound (VOC) profile of carrion. Validation of this dynamic decomposition VOC profile is required in order to characterise the variables that affect their production. This study was performed to determine whether the decomposition VOC profile produced under field conditions differed between summer and winter in an Australian environment. Outdoor studies were conducted using pig carcasses as human analogues in order to assess seasonal variation in the decomposition process. Common decomposition VOCs were identified using comprehensive two-dimensional gas chromatography – time of flight mass spectrometry (GC×GC-TOFMS). Fewer compounds and reduced abundance of VOCs was observed during winter. Relationships between the levels of detected decomposition VOCs and weather variables were established to be stronger in winter. Weak relationships during summer suggested the potential that an underlying variable ( e.g. microbial activity, insect activity) had a stronger relationship to the abundance of decomposition VOCs. The seasonal robustness of the decomposition VOC profile is important to fields relying on the presence of a decomposition odour, i.e. search and recovery of victims in mass disasters, homicides, and missing persons cases.